Improving the Quality of Children's Education with A Teacher-Oriented Education Management Approach Al Mukhlisin Foundation - Siminto, Siminto; Hardianty, Sri; Riyadi, Slamet; Khairunnisa, Dinda; Aprianto, Iwan (Civiliza Publishing, 2024)
The objective of this study is to provide a detailed account of the strategies employed by the teaching staff at Al Mukhlisin Foundation to enhance the quality of learning, to identify the challenges encountered, and to examine the approaches utilized to overcome these obstacles. A qualitative research method with a descriptive approach used in this study. This research employs the principal and teachers as its data sources. The data collection techniques employed in this study are as follows: The research method employed was a combination of three techniques: observation, interview, and documentation. The findings of this study indicate that: It can be stated that the quality of learning at Al Mukhlisin Foundation is enhanced by effective teaching and teacher management. Teachers utilize the 2013 curriculum as a reference point when developing learning plans. Teachers implement learning activities based on the 2020/2021 academic calendar, comprising effective week activities and those conducted on a semester-by-semester basis (odd semester and even semester). The challenges encountered include the limited infrastructure facilities available at Al Mukhlisin Foundation. These include in-focus, teacher handbooks and student handbooks, teaching aids as learning media, and computers in the laboratory. The strategies that teaching teachers apply to improve the quality of learning at Al Mukhlisin Foundation are explained as follows. These include the use of electronic books in the delivery of learning, whereby digital literacy is employed as a substitute for the limited existing facilities, such as in-focus, teacher handbooks, and teaching aids as learning media. Furthermore, teachers in the delivery of learning materials vary existing learning methods, thus creating an active, creative, and enjoyable learning atmosphere.